Social learning and climate change adaptation: evidence for internatio nal development practice - Ensor, Jonathan; Harvey, Blane (Wiley Interdisciplinary Reviews: Climate Change, 2015)
The potential for social learning to address complex, interconnected s ocial and environmental challenges, such as climate change adaptation, is receiving increasing attention in research and practice. Social le arning approaches vary, but commonly include cycles of knowledge shari ng and joint action to co-create knowledge, relationships, and practic es among diverse stakeholders. This results in learning and change tha t goes beyond the individual into communities, networks, or systems. M any authors have focused on analysis of case studies to better underst and the contexts in which such learning occurs. In this paper, we look across this literature to draw out lessons for international developm ent practice. To support those looking to purposively design social le arning interventions for adaptation, we focus on four areas: lessons l earned and the principles adopted when using a social learning approac h, examples of tools and methods used, approaches to evaluating social learning, and examples of its impact. While we identify important les sons for practice within each of these areas, three cross-cutting them es emerge. These are: the importance of developing a shared view among those initiating learning processes of how change might happen and of how social learning fits within it, linking this locus of desired cha nge to the tools employed; the centrality of skilled facilitation and in particular how practitioners may shift toward being participants in the collective learning process; and the need to attend to social dif ference, recognizing the complexity of social relations and the potent ial for less powerful actors to be co-opted in shared decision making. WIREs Clim Change 2015, 6:509–522. doi: 10.1002/wcc.348 This article is categorized under: Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies Climate and Development > Knowledge and Action in Development